Անձի և կազմակերպության համապատասխանության հոգեբանական որոշ ասպեկտներ - Լաուրա Պետրոսյան (ՀՀ ԳԱԱ հրատ.)
There are various behavior forms in an organization. The variety of people, interrelating with different organizational environments, leads to considerable diferences in their behaviour in case of corresponding conditions.
Keywords: Psychology